Применение методов технической теплофизики для расчета температуры при горении подвижного состава в тоннелях метрополитена - Arestovich Дмитрий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The applied method of engineering thermophysics allowed to develop the analytical method for temperature calculation in case of a fire in subway trains in underground tunnels. The calculation for the part on the line between "Borisovsky tract" and "Uruchcha" stations in Minsk underground was made and the time for reliable work of exhaust ventilation systems was determined, including the values of fire thermal depression in the tunnel and ventilation chamber.